Scientific and methodological substantiation of the design of state programs for the provision of temporary housing to the population affected by aggression RF - Sorokina, L.; Shaposhnikova, I.; Stetsenko, S.; Hoiko, A. (Ways to Improve Construction Efficiency, 2022)
The article is devoted to finding ways to solve the problem of providing housing for the population of Ukraine affected by the military conflict in Russia as soon as possible. The institutional preconditions and macroeconomic consequences of slowing down the implementation of the country's reconstruction projects are considered. An analysis of the proposals of leading economists set out in the Essay on the reconstruction of Ukraine. Three fundamental principles of ensuring effective recovery of the Ukrainian economy and reconstruction of damaged and destroyed housing are formulated and their essence is revealed. The author's proposals on the formation of temporary housing funds for internally displaced persons are substantiated and their contribution to restoring the balance of the primary housing market is proved. The causes of imbalances in the construction market of Ukraine are summarized. A methodical approach to the quantitative assessment of the price-quality ratio of housing in new buildings in Ukraine is proposed. 10 criteria were proposed to determine whether new homes meet market requirements. Within each of the criteria, gradation features were substantiated, which are measured in ordinal and nominal scales. A method for calculating the integrated quality indicator of facilities under construction based on data reduction by the method of main factors has been developed. The classification of housing supply in the primary real estate market according to the system of price - quality criteria, the methodological basis of which was neural network modeling using the Kohonen layer. Given the significance of the results obtained, the classification features that allow to separate those objects of market supply that have a low probability of sale in the next 6 to 12 months are justified. An easy-to-use algorithm for the formation of temporary housing funds for internally displaced persons from apartments-factors of market imbalances is proposed.